Chasing Dragons : Security, Identity, and Illicit Drugs in Canada - Grayson, Kyle, 1975- (Book collections on Project MUSE., 2008)
"Chasing Dragons challenges these assumptions of difference and exposes the politics of security in Canada and the policy that they make possible. Focusing on the issues surrounding illicit drugs, Kyle Grayson examines how the discourses and practices of security policy in fact contribute to the construction of Canadian national and cultural identity. This analysis is also relevant beyond Canada. A crucial contribution of this book is to identify the dangers of underestimating the centrality of race and geopolitics to civic conceptions of nationality in liberal societies." "Chasing Dragons reconsiders the meaning of security and discusses avenues for resisting the insecurity produced by liberal states in the post-9/11 world. This critical approach reveals the pervasiveness of power in contemporary Canadian society, how this power is hidden, and the consequences for progressive social politics."--Jacket